Reframing the Debate on Quality vs Quantity in Research Assessment - Pal, Jiban K. (DESIDOC Journal of Library & Information Technology, 2021)
The debate on quality versus quantity is still persistent for methodological considerations. These two approaches are highly contrasting in their epistemology and contrary to each other. A single composite indicator that reasonably senses both quality and quantity would be significant toward performance. This paper evaluates the potency of the combined metric for quality assessment of publications (QP) in India’s National Institutional Research Framework (NIRF) exercise in 2020. It also suggests a potential improvement in quality measurement to obtain the rankings more rationally with finer tunings.